Comparison between direct trocar versus Veress needle for laparoscopic access: a randomized controlled study - Kirti, Divya; Jain, Dinesh; Patil, Kedar; Phalgune, Deepak (International Surgery Journal, 2022)
Background: The existence of numerous techniques for creation of pneumoperitoneum at laparoscopy indicates that none has been proven totally efficacious or complication free. There is dearth of study in India comparing these techniques. The aim of present study was to compare the safety and duration for creating pneumoperitoneum between direct trocar (DT) and Veress needle (VN) technique. Methods: One hundred-fourteen patients aged between 18 and 70 years were included in this single-blind randomized controlled study. Group DT and group VN patients underwent laparoscopic surgery after trocar placement by direct trocar insertion technique and Veress needle technique respectively. The primary outcome measure was the incidence of complications whereas secondary outcome measures were number of items required and time needed to introduce the laparoscope. Intergroup comparison of categorical and continuous variables was done using the Chi-square test/Fisher’s exact test and unpaired t-test respectively. Results: The number of attempts for trocar placement, and complications were comparable between direct trocar and Veress needle group. The mean duration of trocar placement at the first attempt was 102.6 and 142.3 seconds in direct trocar and Veress needle group respectively (p value =0.001). Conclusions: Veress needle is a safe, efficient, and rapid alternative technique as compared to direct trocar.